Genotypic variation for phosphorus uptake and dinitrogen fixation in cowpea on low-phosphorus soils of southern Cameroon - Jemo Martin; Abaidoo R. C; Nolte Christian; Horst Walter J. (Wiley, 2023)
This article is Published by Wiley, 2006 and is also available at DOI: 10.1002/jpln.200520563